2012
DOI: 10.5433/1679-0359.2012v33n4p1539
|View full text |Cite
|
Sign up to set email alerts
|

Celulite juvenil canina – relato de casos

Abstract: ResumoA celulite juvenil ou linfadenite granulomatosa estéril juvenil, é um distúrbio raro que acomete filhotes com idade entre três semanas a seis meses. Os sinais clínicos incluem alopecia, edema, pápulas, pústulas e crostas especialmente em pálpebras. O diagnóstico definitivo requer exames citológico e histopatológico e a terapia precoce e agressiva é preconizada, pois as cicatrizes após recuperação podem ser graves. O tratamento de escolha consiste no uso de altas doses dos glicocorticoides, como prednison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…The detection of JC in an adult animal in the current research was in accordance with previous descriptions that reported the occurrence of this tegumentary pathology in canines aged two to four years, although less frequently (JEFFERS et al, 1995;NEUBER et al, 2004). Diagnosis of JC in older animals is challenging, since it is an unusual condition among adult animals (FILGUEIRA et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The detection of JC in an adult animal in the current research was in accordance with previous descriptions that reported the occurrence of this tegumentary pathology in canines aged two to four years, although less frequently (JEFFERS et al, 1995;NEUBER et al, 2004). Diagnosis of JC in older animals is challenging, since it is an unusual condition among adult animals (FILGUEIRA et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Treatment based on a corticosteroid and an antibiotic promoted the resolution of all pediatric cases, agreeing with other researchers, according to whom the majority of patients recovered under this therapy within three weeks (SCOTT; MILLER, 2007;FONSECA-ALVES et al, 2012). In the adult dog analyzed (case 5) the reduced response to the steroidal anti-inflammatory drugs reflected refractoriness to such immunosuppressive therapy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation